Laparoscopic versus open surgery for gastric cancer: the experience of one European centre - Mindaugas Kiudelis; Aistė Rikterė; Kristina Zviniene; Antanas Mickevicius; Almantas Maleckas; Audrius Ivanauskas; Zilvinas Endzinas (Gastroenterology Review)
Gastric cancer is the third leading cause of cancer death and the fifth most common cancer worldwide: more than a million new cases of gastric cancer are diagnosed every year, with more than 700,000 deaths each year [1, 2]. It causes 1 out of 12 oncological disease-related deaths worldwide. The highest number of new cases is observed in Eastern Asian and Eastern European countries. While incidence rates of gastric cancer in North America, Africa, and South and West Asia are declining, rates in North-East Asia, the Eastern part of South America and Eastern Europe remain high [3]. In Europe, mortality from gastric cancer ranks the fourth among oncological diseases. According to the Lithuanian Cancer Registry, around 1000 people get gastric cancer in this country every year, and over 700 die from relative causes [4]. The 5-year survival rate for patients with this disease is only 25% [4].